Recent advances in regulatory T cell therapy of autoimmunity, graft rejection and cancer - Dunne, Padraig; Fletcher, Jean (My University, 2010)
Since their initial discover in the 1970s and their subsequent resurgence in the mid 1990s, regulatory T (Treg) cells have become one of the most studied cell subsets. Treg cells prevent autoimmunity and limit aggressive immune responses directed against either pathogen or foreign antigen that might serve to damage host tissue. In contrast, tumour cells have been shown to recruit and/or induce Treg cells, which can impair tumour immunity. The immunoregulatory function of these cells makes them ideal therapeutic candidates for the treatment of autoimmune disease and in the prevention of transplant rejection. Likewise, depletion of Treg cells remains an additional option in the treatment of cancer. Despite significant advances in the treatment of murine models of disease with Treg cells, it has been difficult to transfer this success into the clinic. In this review we will discuss relevant patents and the most recent advances in the use of Treg cells to treat autoimmunity, prevent graft rejection as well as the use of anti-bodies to deplete these cells in cancer.
PUBLISHED
PMID: 20812898
Keywords: Immunology; Regulatory T cells (Treg); Immunology, Inflammation & Infection